2019
DOI: 10.1519/jsc.0000000000002635
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Reactive and Maximum Strength Indicators on Sprint Performance

Abstract: Healy, R, Smyth, C, Kenny, IC, and Harrison, AJ. Influence of reactive and maximum strength indicators on sprint performance. J Strength Cond Res XX(X): 000-000, 2018-The primary aim of this study was to assess the relationship between reactive and maximal strength measures with 40 m sprint performance and mechanical properties. Fourteen male and 14 female sprinters participated in this study. On the first day, subjects performed 40 m sprints with 10-m split times recorded in addition to maximal theoretical ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 28 publications
2
27
3
Order By: Relevance
“…The results regarding the sprinting test showed that there is no change in performance across the training period or among groups in general. Sprinting speed is of great importance for achieving success in sports [55]. For example, the presence of short-haul running races (i.e., up to 800 m) which are constantly held in HIFT competitions are associated with success in the sport [5].…”
Section: Discussionmentioning
confidence: 99%
“…The results regarding the sprinting test showed that there is no change in performance across the training period or among groups in general. Sprinting speed is of great importance for achieving success in sports [55]. For example, the presence of short-haul running races (i.e., up to 800 m) which are constantly held in HIFT competitions are associated with success in the sport [5].…”
Section: Discussionmentioning
confidence: 99%
“…Reactive strength index was calculated for the DLDJ and SLDJ as jump height divided by ground contact time. 13 Time to complete the 90° CoD was recorded using speed gates (Smartspeed; Fusion Sport) with a trigger gate 2 m from the start line and an exit gate 2 m to the left and right of the force plates to indicate the end of the maneuver. 21…”
Section: Methodsmentioning
confidence: 99%
“…In a study conducted by Dymond et al in 2011 with 20 rugby players aged 19±2 years, it was stated that there was a high level of positive correlation between RSI and relative strength, and changes in MS could explain approximately 40% of reactive strength. In the study conducted by Healy et al in 2018 with 14 male sprinters with Xage = 22 ± 2 years and 14 female sprinters with Xage = 22 ± 4 years, it was stated that there was no significant relationship between isometric peak power and RSI determined by vertical jump applied from a height of 30 cm 51 . When we compare it with the studies in the literature, it is thought that the reason for the differences in the level of relationship in our research group is due to the isometric measurement tool taken.…”
Section: Discussionmentioning
confidence: 97%